Numerical Investigation of Electrical Efficiency with the Application of Hybrid Nanofluids for Photovoltaic Thermal Systems Contained in a Cavity Channel - Abid A. Memon; M. Asif Memon; Md. Mojammel Haque (Journal of Mathematics)
Photovoltaic thermal systems (PV/T) are devices used to collect both electrical and thermal energies from solar energy. By passing a coolant through flow channels that are connected to the PV/T systems, the temperature of the cells is reduced to enhance their electrical efficiency. Therefore, this study aims at investigating a photovoltaic thermal system via the transport of hybrid nanofluids based on Cu-Al2O3/water. We assume that the flow channel can be considered in two dimensions and is composed of the silicon panel, absorber, and flow channel. The flow channel consists of a cavity along the absorber with a fixed length and a certain height. This will be a combined conduction and convection problem, with conduction occurring on the top two layers of the silicon panel and absorber. Modeling and simulation problems are performed using COMSOL Multiphysics 5.6. The aspect ratio from inlet height to cavity height is defined by Ar, and the volume fraction of Al2O3 is taken double that of Cu. The cell efficiency is analyzed by performing a parametric study by altering the Reynold number (100–1000), inlet temperature (50°C–450°C), the volume fraction of copper (0.01%–10%), and the aspect ratio (0.5, 0.7, 0.9, and 1). It is found that increasing the inlet temperature and aspect ratio decreases the cell efficiency while increasing the Reynolds number and volume fraction increases it. The maximum efficiency of the cell, about 6%, is achieved when the inlet temperature is 50°C, the volume fraction of copper is 10%, Re = 1000, and Ar = 0.5. It was also concluded that when the volume fraction of copper is 0.1, the increase in Reynolds number from 100 to 1000 is improving the cell efficiency by 0.5%. On the other hand, when increasing the volume fraction of copper from minimum to maximum at Re = 1000, the cell efficiency is increasing by 0.3%.